Analysis of goal scoring patterns and passing sequences between winning and losing teams in UEFA-EURO 2012 / Muhamad Safiq Saiful Annur - Saiful Annur, Muhamad Safiq (2013)
Background and purpose of study: The objective of current study is to investigate the differences of winning and losing teams in terms of goal scoring and passing sequences. Methods: Total of 31 matches from UEFA-EURO 2012 were analyzed and 5 matches were excluded from analysis due to matches end up drawn. There are three groups of variable used in the study, which are the goal scoring variable, passing sequences variable and other selected performance indicators. Data were analyzed using Mann Whitney-U Test with significant value set at p < 0.05. Results: Current study found the timing of goal scored was significantly higher for winning team at 1st half (Z- -3.595, p < 0.05) and 2nd half (Z=-3.277,p< 0.05). The scoring frequency was also found to be increase as time progressed and the last 15 minutes of the game was the time interval the most goals scored. The indicators that were significantly differences between winning and losing team were the goal scored (Z= -4.894, p < 0.05), the head (Z= -2.549,p < 0.05), the right foot (Z= -3.546, p< 0.05), comer (Z= -2.307, p < 0.05), open play (Z= -5.022, p < 0.05), inside the penalty box (Z= -5.394,/? < 0.05), attackers (Z= -3,280, p < 0.05) and also the midfielders (Z= -3.823,p< 0.05). Regarding the passing sequences, there are significant difference between both teams in short passing sequences (Z=-.4.899, p < 0.05) and long passing (Z=-.l .958,p < 0.05). The intercept (Z= -2.853, p < 0.05), corner (Z- - 2.307,p < 0.05), poor passing (Z= -2.137, p < 0.05), poor control (Z= -3.026, p < 0.05) and the goalkeeper distribution (Z= -2.329, p < 0.05) resulted in significant difference in how the possession was gained and the possession was significantly gained at 1st quarter (Z- -2.284, p < 0.05), 3rd quarter (Z= -2.941 ,p < 0.05), and 4th quarter (Z= -3.253,p < 0.05). The winning teams preferred to have 2 touches or less and they preferred to use driven shot, inside shot and volley shot in scoring goal (p< 0.05). Regarding the directions of the shot, more goals were scored at lower sections of the goals, either left or right. Conclusion: It can be concluded that the winning teams have significant higher performance indicators in goal scoring compared to losing teams. The data gathered in present study can be used by the coaches to construct detailed training program based on their objectives.